Francis Bacon's hidden hand in Shakespeare's The Merchant of Venice : a study of law, rhetoric, and authorship - Waldman, Christina G., 1957- (Algora Publishing, 2018)
"Whoever wrote 'The Merchant of Venice' had a great legal mind. Was Francis Bacon the author, or one of the authors, of the play? Bacon's deep legal knowledge, even in the civilian law that derived from the Justinian Code, has long been under-appreciated. The author set out to explore whether "Bacon was Bellario," following certain clues, and in the end was led to a more nuanced and surprising understanding linking Bacon to Shakespeare. The other characters are also analyzed, along with a broad set of symbols and puns that provide clues."